IMPACT OF E-BANKING ON CUSTOMER’S SATISFACTION OF PRIVATE BANK - Muhammad Yousuf Sohail (International Journal of Contemporary Issues in Social Sciences, 2024)
Several years ago, e-banking was not a part of the banking industry. Customers had to visit physical bank branches to transfer funds and access various services. However, with the introduction of e-banking in the mid-1990s, it rapidly gained popularity across the globe. While many individuals now use e-banking services, they continue to face challenges such as ATM malfunctions, delayed SMS alerts, network issues, stuck ATM cards, cash shortages, and inefficiencies. Additionally, security concerns and complexities in using online banking applications and websites present further obstacles. The purpose of this study is to examine the impact of e-banking on customer satisfaction within private banks. This research focuses exclusively on private banks and investigates four key factors—user-friendliness, reliability, efficiency, and security & privacy—as independent variables representing e-banking. Customer satisfaction is the dependent variable. Using a quantitative approach, data were collected via questionnaires from 160 private bank customers who use e-banking services. Regression analysis was employed to assess the model, which was found to be a good fit. The results indicate that all four independent variables (user-friendliness, reliability, efficiency, and security & privacy) significantly influence customer satisfaction in private banks. Consequently, these factors are crucial for enhancing customer satisfaction in the e-banking sector of private banks.